X‐ray zooming optics for analyzer‐based multi‐contrast computed tomography. (15th March 2022) - Hirano, Keiichi; Sugiyama, Hiroshi; Nishimura, Ryutaro; Wakabayashi, Daisuke; Suzuki, Yoshio; Igarashi, Noriyuki; Funamori, Nobumasa
Abstract : An X‐ray analyzer‐based optics with a zoom function is proposed for observing various samples with apparent‐absorption contrast, phase contrast and scattering contrast. Proof‐of‐principle experiments were performed and tri‐modal contrast cross‐sectional images of a sample were obtained at 1× and 10× magnification. Abstract : An X‐ray analyzer‐based optics with a zoom function is proposed for observing various samples with apparent‐absorption contrast, phase contrast and scattering contrast. The proposed X‐ray optics consists of a collimator crystal and an analyzer crystal arranged in a nondispersive (+,  −) geometry with a sample placed between them. For the implementation of the zoom function, an asymmetrically cut crystal in the rotated‐inclined geometry was used for the analyzer. Proof‐of‐principle experiments were performed at the vertical wiggler beamline BL‐14B of the Photon Factory. First, the magnification was set to 1×, and then it was zoomed into the optimal magnification (10×). At these magnifications, tri‐modal contrast cross‐sectional images of a sample were obtained by computed tomography. It was confirmed that the image quality at 10× was superior to that at 1×. This achievement opens up new possibilities for observing an entire sample or regions of interest within a sample at optimal magnification, and is expected to be useful for materials science, condensed matter physics, archeology and biomedical science.